Proposal for a Game Design Document model for creating educational games to teach computational thinking - Cruz, Allan Kássio Beckman Soares da; Neto, Carlos de Salles Soares; Teixeira, Mario Meireles; Cruz, Pamela Torres Maia Beckman da; Barbosa, Kleydson Beckman; Brito, Claudiny Priscila Lopes (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.235242, 2023)
This paper proposes a documentation model for game development to accelerate the growth of educational games that promote computational thinking. Computational thinking is an essential skill in today’s world and plays a fundamental role in developing creative solutions and tackling complex problems. Our proposal aims to provide a robust framework for developing educational games that integrate computational thinking concepts in a fun and engaging way. Using this model, we discuss the possibility, effectiveness, and efficiency of using educational games to provide students with a meaningful and enjoyable learning experience related to computational thinking.